Graphing and Measuring COVID-19's First Wave Impact on the Bolivian Economy: Facing the Unknown - Gover Barja (Revista Latinoamericana de Desarrollo Económico, 2021)
The Bolivian monthly index of economic activity along with ARMA models are used in an attempt to graph and measure the impact of COVID-19's pandemic on the Bolivian economy. The accumulated difference between the observed and counterfactual values, show an overall 12.6% loss of economic activity in the 10 months from February to November 2020 of the first COVID-19 wave, with a tilted W-shape short-run recovery just before the beginning of the second wave in December 2020. Breakdown into the twelve Bolivian economic sectors show wide heterogeneity in depth of impact and speeds of recovery during the same period.
Additional information: The author would like to thank Bernardo Fernandez PhD for comments and suggestions at the 5th Applied Research Workshop organized by IISEC in July 2021.
Keywords: 330; Covid-19; ARMA-GARCH Models; Bolivia